Institutions influencing plot access and intergenerational land transfer: policy insights from a smallholder irrigation scheme in Zimbabwe - Parry, K.; Cooper, B.; Bjornlund, H.; Crase, L.; Moyo, M.; Dube, T. (Elsevier, 2025)
Land access is a challenge for young farmers in Africa and likely to become increasingly so, with institutions and intergenerational dynamics a critical influence. Access for existing and would-be young farmers is vital to ensure an age-diverse farming population and support generational renewal on smallholder irrigation schemes. This research adds to the literature on formal and informal institutions impacting plot access and households' perspectives on farm transfer, using a smallholder irrigation scheme in Zimbabwe as a case study site. Qualitative data from interviews with young people, parents and practitioners were analysed by applying the Institutional Analysis and Development framework. The findings firstly illustrate the hybridised and multi-level nature of plot access arrangements, including the flexible leasing arrangements engaged in by young farmers. The data supports the generation of testable hypotheses and theorisation that plot transfer is a staged process, highlighting parents' dilemma of balancing their own and their children's needs and reflecting both inability and reluctance to transfer control. Suggestions for policy and development and further research are highlighted in the conclusion, including the need for schemes to have a strong focus on stimulating rural development, cross-generational approaches to support ongoing land access for young farmers and further research.